Effects of Elastic Band Resistance Exercise on Depression, Stress, and Autonomic Balance when Applied to the Elderly for 12 Weeks: Randomized Controlled Trial (RCT) - et. al., Kim Won Jong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is to determine how a resistance exercise program with an elastic band affects the elderly. Elderly subjects were studied for 12 weeks to determine the program’s effect on depression, stress, and autonomic balance. Methods: There were 30 subjects in the experimental group and 31 subjects in the control group. The experimental group participated in resistance exercise three times a week (Monday, Wednesday, and Friday) for 12 weeks, and the control group did not participate in resistance exercise for 12 weeks. Results: There was no significant difference between the two groups regarding the general characteristics and homogeneity of the dependent variable. There were significant differences in depression and stress, and parasympathetic activity was partially significant but sympathetic activity was not. Conclusion: The resistance exercise program using an elastic band gradually reduced depression and stress over time and helped recover the autonomic nervous system. Therefore, for the elderly, resistance exercise using an elastic band is recommended to reduce depression and stress. We propose a follow-up study to measure the improvement of balance by dualizing the autonomic nervous system into sympathetic and parasympathetic nerves